Pengaruh Model Pembelajaran Project Based Learning Pada Pembelajaran IPS Dalam Meningkatkan Keterampilan Literasi Finansial Siswa Kelas IV Sekolah Dasar - Nurjanah, Indri Januari; Ruatini, Tin; Arifin, Muh. Husen (Educatio, 2026)
This study was motivated by the low financial literacy skills of elementary school students, which stem from the lack of contextual and meaningful learning experiences. Social studies (IPS) instruction tends to remain conventional and does not actively engage students in understanding financial concepts in real-life contexts. Therefore, the Project Based Learning (PjBL) model was implemented to enhance students’ financial literacy through a project involving their roles as sellers and buyers in a Market Class activity. This research aimed to examine the effect of the Project Based Learning (PjBL) model on improving students’ financial literacy skills. The study employed a quasi-experimental method with a pretest-posttest control group design. The results showed that the implementation of the PjBL model had a significant impact on improving the financial literacy of fourth-grade students. This was evidenced by the paired sample t-test in the experimental class, which yielded a significance value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. Additionally, the experimental class achieved an average N-Gain score of 0.84 or 84%, with a minimum score of 0.68 and a maximum of 1.00. Meanwhile, the control class had an average N-Gain score of 0.16 or 16%, with scores ranging from 0.04 to 0.54. Thus, the Project Based Learning (PjBL) model proved to be more effective in enhancing students’ financial literacy skills in social studies learning.